THE IMPLEMENTATION OF PATIENT SAFETY GOALS IN THE INPATIENT DEPARTMENT: AN OVERVIEW - Herni Sulastien; Siti Zuraida Muhsinin; Musniati; Saitun Sapitri (Universitas Karya Husada Semarang, 2024)
Patient safety is a system through which hospitals ensure that patient care is safe and free from undue injuries or potential harm. Implementing patient safety goals is essential to maintaining this safety. This is particularly important in the inpatient department of RSUD Kota Mataram, one of the largest hospitals in the province of NTB, which treats many patients. This study aims to provide an overview of the implementation of patient safety goals in the inpatient department of RSUD Kota Mataram in 2023. The sample for this study consisted of 40 nurses from the inpatient department with descriptive research. Data were collected using a questionnaire with 21 closed statements, and the sampling technique used was total sampling with descriptive analysis. The results show that the implementation of patient safety goals in RSUD Kota Mataram is rated as very good by 39 respondents (97.50%). The results highlight the excellent implementation of patient safety in RSUD Kota Mataram, with 97.50% of respondents implementing patient safety in accordance with standards. The head of the department and all the nurses at RSUD Kota Mataram are committed to continually supporting and improving patient safety practices to enhance patient satisfaction.